2012
DOI: 10.1128/aac.05762-11
|View full text |Cite
|
Sign up to set email alerts
|

ENT1, a Ribavirin Transporter, Plays a Pivotal Role in Antiviral Efficacy of Ribavirin in a Hepatitis C Virus Replication Cell System

Abstract: We previously showed that equilibrative nucleoside transporter 1 (ENT1) is a primary ribavirin transporter in human hepatocytes. However, because the role of this transporter in the antiviral mechanism of the drug remains unclear, the present study aimed to elucidate the role of ENT1 in ribavirin antiviral action. OR6 cells, a hepatitis C virus (HCV) replication system, were used to evaluate both ribavirin uptake and efficacy. The ribavirin transporter in OR6 cells was identified by mRNA expression analyses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…These results based on cell culture experiments are consistent with clinical findings, where it has been observed that individuals with high viral titers are more resistant to combination therapy with IFN-␣ and RBV (34). The mechanism of impaired RBV antiviral activity in persistently HCV-infected cells is related to the reduced expression of ENT1, an RBV transporter, and the reduced uptake of RBV is in agreement with the results of other research reported previously (14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results based on cell culture experiments are consistent with clinical findings, where it has been observed that individuals with high viral titers are more resistant to combination therapy with IFN-␣ and RBV (34). The mechanism of impaired RBV antiviral activity in persistently HCV-infected cells is related to the reduced expression of ENT1, an RBV transporter, and the reduced uptake of RBV is in agreement with the results of other research reported previously (14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that RBV resistance mechanisms in stable HCV replicon cell lines are due to mutations in viral RNA or to defective expression of nucleoside transporters in cells (13,14). Other studies have found that RBV resistance in HCV-infected cell cultures is due to reduced RBV uptake and low expression levels of nucleoside transporters (15)(16)(17)(18). The contribution of cellular factors in RBV resistance mechanisms has been described in HCV and other virus infection models (18,19).…”
mentioning
confidence: 99%
“…14) SLC29A1 mRNA knockdown reduced RBV uptake level in OR6 cells. 15) Thus, mRNA expression is responsible for the transport activity of SLC29A1. Since higher mRNA expression in PBMC may produce higher intracellular uptake and gastrointestinal absorption of RBV, Tsubota's findings that patients with wildtype rs6932345 possessed higher blood RBV and responded well to IFN/RBV therapy might be relevant.…”
Section: Resultsmentioning
confidence: 99%
“…One mutation in NS5A (D320E) conferred a low-level resistance to alisporivir (3.9-fold), probably by reducing the need for cyclophilin A-dependent isomerisation of NS5A. On the other hand, ribavirinresistant HCV replicon cells proved to have a cellular resistance mechanism Page 5 of 73 A c c e p t e d M a n u s c r i p t 5 consisting of a decreased uptake of ribavirin by ENT1 transporters [20]. Here, we wanted to determine whether fluvastatin-resistant HCV replicon containing cells can be selected.…”
Section: Hepatitis C Virus (Hcv) Infection Is a Major Health Burden Wmentioning
confidence: 98%